Pre-Service English Teachers TPACK Framework Understanding Overview - Endang Komariah; Atthaya, Syarifah (U-Jet Unila Journal of English Language Teaching, 2024)
Qualified English language teachers are required to have knowledge about the integration of technology, pedagogy, and content knowledge in their teaching. This research aims at exploring pre-service English language teachers' understanding of the Technology Pedagogy Content Knowledge (TPACK) framework in English Language Teaching. The descriptive qualitative method was used in this study, and data were collected through a standardized questionnaire related to the TPACK framework. The result of this study shows that pre-service English teachers have a high understanding of TPACK (M=3.81). The highest mean of the TPACK aspect is content knowledge (M=3.98), followed by pedagogical knowledge (M=3.92), technological pedagogical content knowledge (M=3.69), and the last is technology knowledge(M=3.65). However, 47.33% of the subjects do not use technology frequently in teaching English, 56.67% get problems in helping others to coordinate the use of content, technologies, and teaching approaches at school, 72.6 % cannot select appropriate technologies to use in the classroom that enhance what to teach, how to teach, and what students learn, and only 57.33% apply various knowledges in teaching speaking.  It can be concluded that the pre-service teachers have shown their awareness of the importance of TPACK in the teaching and learning process though they still have problems in some aspects. Pre-service English teachers are recommended to use technology by modifying technology and literacy to promote the quality of the teaching and learning outcomes. Other researchers can focus on TPACK implementation in the classroom to compare the understanding of the framework and its practice in the field.